(untitled) (Canadian Medical Education Journal, 2020)
Background: Regional medical campuses (RMC) have shown promise in addressing physician shortages. RMCs have been positively evaluated in rural/remote communities, however, it is unclear whether this model will be as beneficial in underserved urban areas. This study evaluated the impact of a RMC on a midsized urban city (Windsor, Ontario). We compare our results with a similar study conducted in a remote community in British Columbia (BC). Methods: A broad array of community stakeholders representing different sectors were consulted using a semi-structured interview format replicated from the BC Northern Medical Program (NMP) study. Thematic analysis based on the resulting rich data was conducted within a grounded theory context. Results: Twenty-three participants (52% male) representing healthcare, education, business, community and government/politico sectors were consulted. Their views regarding the Windsor Regional Medical Campus (WRMC) aligned around several themes: improved healthcare, enhanced community reputation, stimulated economic/community development, expanded training opportunities and an engaged community regarding the WRMC. These results were compared to the main findings of the NMP study with both similarities (e.g. increased community pride) and differences (e.g. resource concerns) discussed. Conclusion: Community stakeholders provided strong support for the WRMC through their perceptions of its positive impact on this urban region. These findings are consistent with similar RMC studies in rural/remote areas. Those interested in developing a RMC might benefit from considering these findings.